SAT0485 Patiens with Early-Onset Juvenile Spondyloarthropaties: A Distinct Population. (9th June 2015) - Katsicas, M.M.; Russo, R.A.
Abstract : Background: The Juvenile spondyloarthropaties (JSpA) are a group of related, clinically heterogeneous, seronegative rheumatic diseases. Usually disease onset occurs in late childhood (after 8 years) 1 or adolescence. However, younger patients have been reported, making its diagnosis difficult at an early age. There is sparse information about the clinical features of JSpA in patients with disease onset before 8 years. Objectives: To describe and analyze disease features at onset and during the disease course in patients with JSpA starting before 8 years. To compare such characteristics with patients with disease onset after 8 years. Methods: Retrospective analysis of clinical data obtained from patients with JSpA (defined as ERA, JPsA or UA according to ILAR) followed in a tertiary center. Patiens were divided into 2 groups: disease onset ≤8 yo and disease onset >8 yo. Recorded variables included: age at onset, sex, disease duration before first visit; clinical features at disease onset and during disease course: number of active joints, number of limited joints, articular pattern (symmetric-asymmetric, oigoarticular/polyarticular, small/large joints and upper/lower limbs), axial involvement (limitation of lumbar spine motion, low back pain), presence of enthesitis, tarsitis, dactylitis, uveitis, radiologic sacroiliitis, diarrhea, urethritis, psoriasis, inflammatory bowel disease, fever, positive HLAB-27 and family history, lowest hemoglobin level, highest erythrocyte sedimentation rate (ESR). Outcome measures (at last visit): activity (BASDAI) and functional capacity (BASFI and CHAQ), use of biologics and presence of bone damage. Chi square and Mann-Whitney tests were used for comparisons Results: 110 patiens with JSpA followed for median 7 years were included (M: 96, 87%). Disease onset ≤8 y.o ocurred in 20 (18%) children. Age at onset was 6 (1-8) y in the early onset group and 11 (9-16)y in the later onset group. Diagnosis delay (8 vs 6 months) was similar. Patients with disease onset ≤8 y differed from patients with disease onset >8 y in: articular pattern (symmetric 45% vs 22%, p=0.04) and polyarticular (40% vs 14%, p=0.0097), dactylitis (25% vs 8%, p=0.024), uveitis (25% vs 3%, p=0.0048), positive HLA B-27 (60% vs 20%, p=0.0007), lowest hemoglobin (11 g/dl vs 12.5 g/dl, p=0.0004), ESR (55 mm/h vs 28.5 mm/h, p=0.047) at onset. During disease course patients showed differences in: sacroiilitis (50% vs 22%, p=0.0003), persistent dactylitis (25% vs 7%, p=0.0049), radiographic bone damage (25% vs 7%, p=0.03) and use of biologics (55% vs 21%, p=0.0036). No differences in activity and functional capacity outcomes were found between both groups. Conclusions: JSpA patients with disease onset before 8 yo show more inflammatory features at disease onset. These findings seem to identify a distinct population. Recognizing these findings at onset would allow a correct classification of younger patients with JSpA. References: Petty RE, Southwood TR, Baum J; Bhettay E, Glass DN, Manners P, Maldonado-Cocco J, Suarez-Almazor M, Orosco-Alcala J, Prier AM. Revision of the proposed classification criteria for juvenile idiopathic arthritis: Durban, 1997. J Rheumatol 1998 Oct;25(10):1991-4. Disclosure of Interest: None declared